Tomorrow there will be sun [large type] - Reinhardt, Dana (Thorndike Press large print core, 2019)
"A private Mexican villa is the backdrop to a hilarious, smart story of a milestone vacation in a tropical paradise gone wrong, wrong, wrong. Two families arrive in Puerto Vallarta, Mexico, for a once-in-a-lifetime vacation. The resort town is known for its stunning views, exotic wildlife, and welcoming locals, and Jenna has organized the trip to celebrate her husband's fiftieth birthday--she's been looking forward to it for months. Their friends the Solomons can be overbearing at times, but Jenna is sure everything is going to be just perfect--and the margarita refills delivered by the house staff certainly don't hurt, either. What could go wrong? Yet as the families settle into their vacation routines, their best friends suddenly seem like annoying strangers, and even Jenna's reliable husband, Peter, seems to be staying up late with his friend Solly and sharing clandestine phone calls with someone--but who? Jenna's teenage daughter, Clem, is spending an awful lot of time with Malcolm, Solly's son, whose questionable rep got him expelled from school. Jenna's dream of the ultimate celebration begins to crack and eventually crumbles completely, leaving her wondering whom she can trust, and whether her privileged life is about to be changed forever"--